Sequential Recurrent Encoders for Land Cover Mapping in the Brazilian Amazon using MODIS Imagery and Auxiliary Datasets - Coca-Castro, Alejandro; Rußwurm, Marc; Reymondin, Louis; Mulligan, Mark (2019)
To test an existing sequential recurrent encoders model based on convolutional variants of RNNs for the task of LUC classification across the Brazilian Amazon and to compare different arrangements of input features and their impact on the classifier performance